4D printing of shape memory polylactic acid (PLA) components: Investigating the role of the operational parameters in fused deposition modelling (FDM). (January 2021) - Barletta, M.; Gisario, A.; Mehrpouya, M.
Abstract: Shape Memory Polymers (SMPs) are attracting considerable interest both in the scientific and industrial fields. Among them, polylactic acid (PLA) is particularly appreciated, as it is a bioderivation polymer, biodegradable and compostable with high thicknesses, with excellent shape memory properties, which can be activated by varying the temperature of the material across the glass transition temperature. In this study, PLA is used in the 4D printing process for the manufacturing of complex geometry components by Fused Deposition Modelling (FDM), with a potential as stress-absorbers. The shape memory properties of the manufactured component have been tested varying the operational parameters of the printing process (i.e., the temperature at the nozzle, the deposition speed, the layer thickness) as well as the activation temperature that allows the recovery of the initial shape. In particular, the time needed to recover the shape and the percentage of recovery with respect to the initial shape were assessed. Experimental results have shown that PLA components have adequate shape memory properties, with short recovery times and high recovery rates being easily achievable. Among process parameters, the activation temperature is found to be the most significant parameter to trigger the recovery of the initial shape in the shortest possible time.